Potential Yield Loss Of Short term Crops Due To Ozone Exposure - Jie, Michael Bong Wen (2010)
This research is to investigate the effect of air pollution to crop production. Air pollution is the major pollution can cause adverse impact to the crops as well as human health. Ozone (O3) is a secondary pollutant which may affect the crops yield lost where NO2 act as precursor for O3 formation. There are three sites involved in this study which are Taiping, Perai and USM. The crops reductions due to O3 exposure in certain concentration standard were based on AOT40 which is the European benchmark for the crop study. AOT40 can be defined as the accumulations of the O3 concentration exceed 40 ppm for three months period. Crops yield loss can go up to 5% when the AOT40 exceed 3000ppm accumulation limit. There are five crops involved in the study which are spinach, long bean, lady‘s finger, chili and maize. Total yield loss for the five crops is 439.911 metric tonnes and 448.409 metric tonnes for 2004 and 2005 respectively. Hence, O3 formation for these three sites was analyzed where NO2 is the precursor. The O3 prediction models for each sites were generated. Other meteorological parameter such as temperature, wind speed and humidity were involved in the modeling. The models were generated based on the AOT40 values which are calculated in every three month period. Ten models were generated for each site for 2004 and 2005. There are some steps which involved in the modeling process. First, the model should be generated. Then, justification of the model was carried out to test the performance of the model by using scatter plot and performance indicator. From this step, the best model for each site can be determined.Site sampling for each site were carried out in order to verify the model.